The experience and substance of aquatic activities learning in elementary schools from the perspective of physical education teachers - Hedi Ardiyanto Hermawan; Subagyo Subagyo; Nur Sita Utami (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
The objective of this phenomenological research is to describe the substance of aquatic activities learning based on the experience of elementary school physical education teachers in Yogyakarta City in carrying out aquatic activities learning. Ten elementary school physical education teachers in Yogyakarta City agreed to participate in this study. The research subjects were selected with the snowball sampling technique. A qualitative approach was used in data collection and data analysis. Open interviews were conducted based on the interview guide instrument. Data analysis techniques based on the Miles and Huberman model include data reduction, data display, and conclusion drawing/verification. The data obtained are the experience of physical education teachers in carrying out aquatic activities learning and the substance of aquatic activities learning for physical education teachers. Every word during the interview was recorded and rewritten for further analysis. The grouping process used Atlas.ti 22 software. The themes that emerge from the analysis consist of: (1) the learning process of aquatic activities; (2) parental support; (3) obstacles to learning aquatic activities; and (4) the substance of aquatic activities learning. The researchers see this phenomenon based on the Theory of Planned Behavior. The teachers’ decision to conduct aquatic activities learning does not depend on its substantiality only. However, aquatic activities learning needs the support of parents and schools.